Cachrys pungens Jan inhibits human melanoma cell proliferation through photo‐induced cytotoxic activity - Menichini, G. (Cell Prolif, 2011)
Objective:  To date, plants belonging to the genus Cachrys have not been amply studied. In the present study, aerial components of Cachrys pungens Jan from Italy, were examined to assess their free radical‐scavenging and antioxidant activity, and their phototoxicity on A375 melanoma cells. In view of potential pharmaceutical applications, a relationship between antioxidant, phototoxic activities and polyphenolic composition has also been investigated. Materials and methods:  Content of sterols, terpenes, fatty acids and coumarins was assessed by gas chromatography–mass spectrometry and GC. Total phenolic content was also determined. Antioxidant activity of the methanol extract and fractions of C. pungens Jan was assessed using DPPH scavenging assay and β‐carotene bleaching test. Plant phototoxicity was also investigated in this human tumour cell line (amelanotic melanoma). Results:  Analysis of the chloroform extract was particularly interesting, as it led to identification of many coumarins, of which five were linear and one angular furanocoumarins. Methanol and ethyl acetate fractions exhibited substantial antioxidant activity. Moreover, chloroform extract and isolated coumarin fraction had strong phototoxic activity on UVA‐induced A375 cells after irradiation at UVA dose of 1.08 J/cm. Conclusions:  Plant‐derived natural compounds are an important source for development of cancer‐fighting drugs. This study has demonstrated strong phototoxic activity of the coumarin fraction of C. pungens, a plant which, to our knowledge, has never been studied before. This investigation offers a new perspective for developing other formulations potentially useful in photodynamic therapy for treatment of non‐melanoma skin cancers as well as melanomas.